PARTISIPASI MASYARAKAT DALAM AKSI KONVERGENSI PENANGANAN STUNTING DI KABUPATEN BLITAR - Sri Juni Woro Astuti; Esa Wahyu Endarti; Diana Heni Lestari (Jurnal Gesi, 2023)
Stunting is a serious issue that requires attention from all stakeholders, including both government agencies and the public on a local level. Due to this, Indonesian Government has announced eight convergences action to reduce stunting prevalence become 14% in 2024. So all stakeholers are expected to make preventing stunting a top priority in each individual region's agenda for human development. With the intention of making the execution of this particular act of convergence more effective, the participation will become a crucial factor. For this reason, the focus of the current study is to determine how the society and privat sector will participate in upcoming convergence activities. The research was conducted in Blitar district as one of the areas with relatively low stunting rates so it is hoped that it will become best practice research. The research method uses descriptive qualitative and data collection through interviews and secondary data. The analysis is based on the participation ladder theory, and shows that only a few activities from the convergence action involve public and private participation. So researchers recommend that the community really be the main actor in this convergence action so that stunting reduction is achieved. Key Words: Participation, Convergence, Stunting